Three new and notes on two other jumping spider species of the genus Stenaelurillus Simon, 1886 (Salticidae: Aelurillina) from the Deccan Plateau, India - Marathe, Kiran; Sanap, Rajesh; Joglekar, Anuradha; Caleb, John T. D.; Maddison, Wayne P. (Zootaxa, 2022)
We describe three new species of Stenaelurillus Simon, 1886 from the Deccan Plateau of India, and report on populations of S. sarojinae Caleb & Mathai, 2014 and S. marusiki Logunov, 2001. One of the new species, S. shwetamukhi Marathe, Sanap, & Maddison, sp. nov., has black-and-white markings, characteristic of several other Indian Stenaelurillus species. The other two new species, S. tamravarni Marathe & Maddison, sp. nov., and S. vyaghri Sanap, Joglekar, & Caleb, sp. nov., are colourful and with fringed male abdomens, like several other Indian species including S. sarojinae. The population of S. sarojinae from Mysuru, Karnataka, shows colours distinct from the population at the type locality. The female of S. marusiki is described for the first time.